Successful redo aortic valve replacement using Perceval valve in a patient with prosthetic valve endocarditis complicated by acute cerebral infarction - Goto, Takasumi (Ann Med Surg (Lond), 2021)
INTRODUCTION: and importance: For treatment of prosthetic valve endocarditis (PVE), redo-aortic valve replacement (AVR) is usually required. However, the recurrence of PVE continues to be a serious problem that needs a solution. CASE PRESENTATION: An 83-year-old woman who had undergone AVR for aortic infective endocarditis 12 years ago was diagnosed with PVE complicated with acute cerebral infarction. Urgent redo-AVR was performed. After complete removal of the prosthesis, Perceval S valve was implanted successfully. There were no postoperative neurological deteriorations, and the echocardiogram showed no recurrence of PVE. CLINICAL DISCUSSION: Theoretically, the fewer prostheses left in the heart, the lower the risk of PVE recurrence. CONCLUSION: In patients with PVE, redo-AVR using the Perceval valve may be a suitable option since Perceval reduces the prosthesis in the heart compared with conventional redo-AVR.